PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA TOKO BUKU SINAR ABADI - Adya Ramadhani; Alin Nasuha; Elis Nurhasanah; Iwan Giri Waluyo (Shofanah Media Berkah, 2023)
In the current digital era, the use of information technology is very important in running a business. One form of information technology that can be utilized is a web-based information system. Bookstores as a business engaged in selling books, need to utilize information technology to increase efficiency and effectiveness in managing their business. Sinar Abadi Bookstore is one of the bookstores in big cities. In running its business, this store still uses traditional ways of recording sales such as recording purchases manually, keeping track of stock, and so on. Therefore, it is necessary to create a website-based sales information system that can assist Sinar Abadi Bookstore in managing sales data effectively and efficiently. In this case, the purpose of this research is to design and develop a web-based sales information system at the Sinar Abadi Bookstore. Of course, with the limitation of the problem, namely the website administrator plays an important role in creating, adding, or changing the data displayed on the web. The result of this research is a website about a sales information system that answers problems at the Sinar Abadi Bookstore.